When calls the heart. Rules of engagement [videorecording (DVD)] - Fearnley, Neill; Krakow, Erin; Wagner, Jack, 1959-; Brolin, James, 1940-; Lissing, Daniel, 1981-; Loughlin, Lori; Oke, Janette, 1935- (When calls the heart, 2014)
"A surprise arrival shakes things up in the sixth When Calls the Heart film. Just when Elizabeth (Erin Krakow) thinks she has Jack (Daniel Lissing) back for good, a beautiful woman arrives in Coal Valley threatening to ruin their budding love. Saddened by the turn of events, Elizabeth considers a job offer back east. Another visitor, inspector Bill Avery, sends waves through the town as he helps Jack uncover what really led to the mine explosion. With townspeople pointing fingers at each other and tensions at an all-time high, Abigail (Lori Loughlin), Jack and Elizabeth are forced to make difficult decisions in life and love that will change their paths forever."--Container.